Outcomes of Primary versus Multiple-Staged Repair in Hirschsprung's Disease in England - Giuliani, Stefano; Honeyford, Kate; Chang, Chieh-Yu; Bottle, Alex; Aylin, Paul (European Journal of Pediatric Surgery, 2020)
Introduction The study aimed to compare 1-year outcomes for primary versus multiple-staged (three operations with colostomy) repairs in Hirschsprung's disease (HD).Materials and Methods Retrospective analysis of a large national administrative database (Hospital Episode Statistics) including all the neonates born with HD in England between 2003 and 2015. Main outcomes were: 1-year mortality, postoperative readmissions, and reoperations. Secondary outcomes: cumulative length of hospital stay (cLOS) and hospital volume–outcome relationship.Results A total of 1,333 neonates with HD were treated in 21 specialist pediatric surgical centers; 874 (65.5%) patients had a primary repair for HD. One-year mortality was 2.8%. The overall readmission rate was 70.2%, with a significant difference between primary and multiple-staged repair (79.9 vs. 90.1%, p < 0.01). There was no difference in reoperation. Primary pull-through was associated with a significantly lower probability of postoperative readmission (odds ratio [OR] = 0.08, 95% confidence interval [CI] = 0.06–0.11, p < 0.001) and cLOS (OR = 0.38, 95% CI = 0.28–0.52, p < 0.001) compared with multiple-staged repair. There were no significant difference in outcomes between patients treated in low-volume (<37 cases/year) and high-volume (> 55 cases/year) specialist centers.Conclusion Whenever clinically indicated, primary repair should be used in HD as this is associated with fewer readmissions and shorter time spent in the hospital.
Keywords: Hirschsprung's disease; outcomes; primary repair; multiple-staged; length of stay